POTENTIALLY TOXIC METALS, SEDIMENT–WATER PARTITIONING AND ECOLOGICAL RISK ASSESSMENT IN A TROPICAL INDUSTRIAL DRAINAGE SYSTEM: IMPLICATIONS FOR REMEDIATION STRATEGIES IN LAGOS, NIGERIA - Kuteyi, Temitayo Richard; Akinsanya, Nurudeen Akinwale; Awonubi, Christopher Opeoluwa (FUDMA Journal of Sciences, 2026)
The drainage canal within the Ikeja industrial area along the Agidingbi axis in Lagos, Nigeria serves as a major receptor for effluents generated from surrounding industrial and residential activities. This study evaluated the physicochemical characteristics and concentrations of selected potentially toxic metals in wastewater and canal sediments. Wastewater and sediment samples were collected from upstream and downstream locations during morning and evening periods over five consecutive days between October and November 2023. Physicochemical parameters were determined using standard analytical procedures, while metal concentrations were quantified using inductively coupled plasma atomic emission spectrometry (ICP-AES). The results revealed pH values ranging from 6.25 to 8.80, temperatures between 29.0 and 31.0 °C, electrical conductivity of 422–1035 µS/cm, biological oxygen demand (BOD) of 34–100 mg/L, and chemical oxygen demand (COD) of 233–973 mg/L. While pH, temperature, and BOD largely complied with National Environmental Standards and Regulations Enforcement Agency (NESREA) limits, conductivity and COD exceeded recommended thresholds. Mean concentrations of Cd, Cr, Fe, Pb, and Zn in wastewater were within regulatory limits, whereas iron concentrations in sediments exceeded permissible values. The results indicate progressive environmental stress within the Agidingbi industrial corridor, driven primarily by sustained industrial and domestic discharges (Figure 1).